The role of intradermal proliferation of T-cells in the pathogenesis of psoriasis - Vladislav R. Khairutdinov; Anastasiya F. Mikhailichenko; Irena E. Belousova; Ekatherina Sh. Kuligina; Alexey V. Samtsov; Evgeny N. Imyanitov (Sociedade Brasileira de Dermatologia, 2017)
Abstract: BACKGROUND: Psoriasis is a common immune-mediated chronic inflammatory disease of the skin and joints, affecting 1-3% of the population. It is generally accepted that the pathogenesis of psoriasis involves accumulation of effector T-cells within lymph nodes and their subsequent migration into the skin through the blood system. Here we provide evidence that psoriatic plaque itself may serve as a source of inflammatory T-cells. OBJECTIVE: We examined the intradermal proliferation of T-cells and the number of effector/memory (CD45RO+) T-cells in the skin of psoriatic patients at different periods of the disease. METHODS: Skin samples were obtained from 41 patients with progressive psoriatic lesions; 18 of these patients also donated skin specimens during the remission of the disease. The control group consisted of 16 healthy subjects. Ki-67 immunohistochemical staining was applied to detect proliferating cells, CD3ε served as a T-cell marker, and CD45RA and CD45RO antibodies were utilized to discriminate between naive and effector/memory T-cells, respectively. RESULTS: Progressive psoriatic lesions demonstrated Ki67 staining both in keratinocytes and in the CD3ε+ cells of dermal infiltrate. Median count of CD45RO+ cells per microscopic field was 15 in healthy controls, 59 in patients in remission and 208 in progressive psoriatic plaques. The observed differences demonstrated high level of statistical significance. STUDY LIMITATIONS: Limited number of analyzed patients. CONCLUSION: Progressive phase of psoriasis is characterized by intradermal proliferation of T-cells. Spots of regressed psoriatic lesions contain high number of CD45RO+ cells, which are likely to render an immunological memory.